ปัจจัยทางเศรษฐกิจสังคมที่มีผลต่อการใช้ประโยชน์ทรัพยากรป่าไม้ : ศึกษากรณีชุมชนรอบป่าดงนาทาม จังหวัดอุบลราชธานี - บุญทวี บุญโญ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The main purpose of this research was to study the social and economic factors influencing the use of forest resources by using six variables namely: occupation, income, education, ownership of the land, term of staying in the communities and the responses on protecting the forest. The communities around Dongnatam forest in Srimuengmai district and Kongjiam district were chosen for this study. Two hundred households were selected as the sample size out of 775 households. The data was analyzed by using questionnaire, documentary study, general observation informal interview, in-depth interview, percentage and the SPSS program with 0.05 significant level. The hypotheses were as follows : 1. Breadwinners who were the farmers had more use of forest than the ones who were not the farmers 2. Families with high income had less use of forest than the ones with low income. 3. High educated breadwinners had less use of forest than the low educated ones. 4. Families who were the owner of the land had less use of forest than the ones who were not the owner of the land. 5. Families with long term of staying in the communities had more use of forest than the ones with short term of staying in the communities. 6. Families which had good responses on protecting the forest had less use of forest than the ones with poor responses on protecting the forest. The results of the research were in accordance with all hypotheses.